Evaluation of morphometric parameters of the optic disc in patients with diverse clinical forms of openangle glaucoma - L. L. Arutyunyan; Yu. S. Morozova; S. Yu. Anisimova; S. I. Anisimov (Российский офтальмологический журнал, 2022)
Purpose. To compare the thickness of the prelaminar layer of nerve fibers and the depth of the lamina cribrosa in patients with diverse forms of open-angle glaucoma, measured by optical coherence tomography (OCT).Material and methods. 130 patients aged 71.4 ± 9.7 with stage II (advanced) glaucoma were divided into three groups depending on the form of glaucoma: group 1 of 39 patients with primary openangle glaucoma (POAG); group 2 of 26 patients with normal-tension glaucoma (NTG); group 3 of 22 patients with pseudoexfoliative glaucoma (PEG). The control group consisted of 43 patients without ophthalmic pathology. All patients were scanned for the optic disc and the macular areas in the OCT Disk + Macula 3D regimen and in the Disk Raster regimen (Optopol Revo 60 OCT device (Optopol Technology, Poland). The depth of the lamina cribrosa (LC) and the thickness of the prelaminar layer of nerve fibers (tPLNF) were calculated.Results. No significant differences were found between the LC depth in patients with different forms of glaucoma compared with the control group. LC depth averaged 426.9 ± 98.7 μm (p < 0.164) in patients with POAG, 416.9 ± 161.0 μm (p < 0.818) with NTG and 425.5 ± 88.04 μm, (p < 0.18) with PEG. The thinnest layer of prelaminar nerve fibers was found in patients with NTG (134,0 ± 91.4 μM), where the value was half as much as the control (p < 0.001). There were no differences in the tPNFL parameter in POAG (193.2 ± 114.6 μm) and PEG (190.7 ± 115.3 μm) but both were significantly lower as compared to the control group (p < 0.001, p < 0.002) respectively.Conclusion. The study of LC parameters contributes to a better understanding of the pathogenesis of optic neuropathy in diverse forms of glaucoma. It opens up new opportunities in the differential diagnosis and prediction of the glaucoma course.